Conhecimento, currículo e política educacional: a proposta de ensino de Educação Física para a escola pública do Paraná, Brasil, anos 90 - Fratti, Rodrigo Graboski (2001)
This paper aims to investigate which theoretical-methodological elements of scientific production in Physical Education of the 1980s were incorporated into the proposal of teaching Physical Education of the Basic Curriculum for the Paraná Public School, elaborated in 1990, and how the process took place. incorporating these elements. Immersing itself in the Brazilian historical, political and educational context, it initially presents the panorama of scientific production in Physical Education in the 1980s. It then analyzes the political-educational framework in the state of Paraná in the late 1980s and early 1980s. 90. It also deals with the texts that compose the Physical Education teaching proposal of the Basic Curriculum of the Paraná Public School, in order to grasp the limits and advances contained in this curricular proposal. Methodologically, it was decided to work with documentary sources, highlighting, in addition to official documents of the Paraná State Department of Education, articles and other publications published in the Brazilian Journal of Sports Science, especially those published in the period investigated here. For the analysis of the data collected from the searched sources we resorted to the content analysis. It is concluded that the curricular proposal analyzed, despite surpassing the biologicist model of Physical Education, also shows the coexistence of different philosophical and theoretical-methodological matrices. Therefore, this study is part of the research field that discusses the different academic, scientific, political and school knowledge that inform the educational policies today.